PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR LOGAM YANG TERDAFTAR DI BURSA EFEK INDONESIA 2020 – 2024 - Salihi, Said Saleh; Mujanah, Siti; Malik, Abdul (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the factors that influence stock prices of metal subsector companies listed on the Indonesia Stock Exchange, focusing on the effects of the Current Ratio and Debt to Equity Ratio. A quantitative approach was used, relying on secondary data obtained from the Indonesia Stock Exchange for the 2020–2024 period. Data were collected through literature review and document analysis. The sample was selected using purposive sampling, resulting in 12 companies out of 34 issuers after applying specific criteria. The data were analyzed using multiple linear regression. The findings indicate that the Current Ratio and Debt to Equity Ratio simultaneously have a significant effect on stock prices in the metal subsector. Furthermore, the Debt to Equity Ratio shows a more dominant influence, highlighting that leverage is an important factor in determining stock value for companies in the metal and mineral subsector. These results emphasize that liquidity and capital structure play a crucial role in market valuation.